Kualitas Konten sebagai Moderator Pengaruh Media Instagram dan Brand Ambassador Skintific - Mega Sihombing; Febriansyah Febriansyah (Penerbit Goodwood, 2025)
Purpose: This study aims to examine the role of content quality as a moderation variable in social media variables and brand ambassadors to Skintific product brand awareness. Methodology/approach: This study uses a quantitative approach with a causal research design. The sampling technique uses purposive sampling with a sample of 100 people. Data were collected via a Google Form questionnaire and analyzed using SmartPLS version 3.3. Results/findings: The results of the study are as follows: social media variables affect brand awareness of Skintific products, brand ambassadors influence brand awareness of Skintific products, content quality is able to strengthen the influence of social media on brand awareness of Skintific products and content quality is able to strengthen the influence of brand ambassadors on brand awareness of Skintific products. Conclusion: Content quality significantly strengthens the impact of social media and brand ambassadors on brand awareness, maximizing the effectiveness of digital marketing on consumer perceptions. Limitations: This research also has limitations in the coverage of the area focused on the city of Bandar Lampung; therefore, future similar research can expand the scope of the research area to obtain better results. Contribution: Companies pay more attention and strive to maintain and increase brand awareness or consumer brand awareness of products so that consumers make the brand their first choice when they want to buy products.